2020
DOI: 10.3390/met10121697
|View full text |Cite
|
Sign up to set email alerts
|

Control of Density and Grain Structure of a Laser Powder Bed-Fused Superelastic Ti-18Zr-14Nb Alloy: Simulation-Driven Process Mapping

Abstract: This study focuses on the control of density and grain structure of a superelastic Ti-18Zr-14Nb (at. %) alloy subjected to laser powder bed fusion. It starts with the production and characterization of a Ti-18Zr-14Nb powder feedstock and printing of a series of calibration specimens. These specimens are next subjected to chemical, structural, phase and texture analyses in order to collect experimental data needed to build simulation-driven processing maps in the laser energy density–material build rate coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Against this background and paying attention to the latest developments, Ewald et al [5] innovatively applied laser powder bed fusion to produce crack-free samples of a low-cost Fe-based SMA and achieved a good shape recovery by means of an optimized heat treatment route. Applying a different approach to achieve optimized materials, Brailovski et al [6] demonstrated that simulation-driven processing maps can be used to relate the main laser powder bed fusion parameters to the control of density and grain structure of superelastic Ti-18Zr-14Nb alloys. To complete this section of the Special Issue, NiTi, as the most successful SMA, also produced via additive manufacturing could not be absent.…”
Section: Contributionsmentioning
confidence: 99%
“…Against this background and paying attention to the latest developments, Ewald et al [5] innovatively applied laser powder bed fusion to produce crack-free samples of a low-cost Fe-based SMA and achieved a good shape recovery by means of an optimized heat treatment route. Applying a different approach to achieve optimized materials, Brailovski et al [6] demonstrated that simulation-driven processing maps can be used to relate the main laser powder bed fusion parameters to the control of density and grain structure of superelastic Ti-18Zr-14Nb alloys. To complete this section of the Special Issue, NiTi, as the most successful SMA, also produced via additive manufacturing could not be absent.…”
Section: Contributionsmentioning
confidence: 99%